Mircea Eliade e la realtà dei poteri paranormali - Ermacora, Davide (Studi e materiali di storia delle religioni, 2015)
In 1937 Mircea Eliade published the article Folclorul ca instrument de cunoaştere («Folklore as an instrument of knowledge») in which he affirmed the need to investigate the reality of paranormal phenomena (levitation, the body's ability to resist fire etc.). This text was little read in the West until the late 1970s, when a French translation appeared. The present study is an updated contribution to this peculiar chapter in Eliade's intellectual history. Through a critical dialogue with some recent publications and trying to contextualize the article through Eliade's work on India, I will take into consideration several crucial aspects in the making of the Romanian scholar: 1) his early works from the 1920s, as harbingers of the 1937 article; 2) the relationship between Eliade and Ernesto de Martino (1908-1965) concerning the reality of magical powers; 3) and his formative relations with Giovanni Papini (1881-1956) and Vittorio Macchioro (1880-1958), decisive in Eliade's early Italian intellectual formation. Finally, relying on unpublished material from the Macchioro Archive at the University of Trieste, I analyze Macchioro's interest in spiritualism, the paranormal and the academic study and spread of yoga in Italy in the first half of the twentieth century. (English)